UNC-83 Is a KASH Protein Required for Nuclear Migration and Is Recruited to the Outer Nuclear Membrane by a Physical Interaction with the SUN Protein UNC-84 - McGee, Matthew D. (The American Society for Cell Biology, 2006)
UNC-84 is required to localize UNC-83 to the nuclear envelope where it functions during nuclear migration. A KASH domain in UNC-83 was identified. KASH domains are conserved in the nuclear envelope proteins Syne/nesprins, Klarsicht, MSP-300, and ANC-1. Caenorhabditis elegans UNC-83 was shown to localize to the outer nuclear membrane and UNC-84 to the inner nuclear membrane in transfected mammalian cells, suggesting the KASH and SUN protein targeting mechanisms are conserved. Deletion of the KASH domain of UNC-83 blocked nuclear migration and localization to the C. elegans nuclear envelope. Some point mutations in the UNC-83 KASH domain disrupted nuclear migration, even if they localized normally. At least two separable portions of the C-terminal half of UNC-84 were found to interact with the UNC-83 KASH domain in a membrane-bound, split-ubiquitin yeast two-hybrid system. However, the SUN domain was essential for UNC-84 function and UNC-83 localization in vivo. These data support the model that KASH and SUN proteins bridge the nuclear envelope, connecting the nuclear lamina to cytoskeletal components. This mechanism seems conserved across eukaryotes and is the first proposed mechanism to target proteins specifically to the outer nuclear membrane.